Factors Affecting the Uptake of Life Insurance in Botswana - Malambo, Maalila; Qutieshat, Abubaker (Rescollacom (Research Collaborations Community), 2024)
The low uptake of life insurance is a matter of significant concern both within Africa and globally due to its aims to investigate the factors contributing to the poor adoption of life insurance products in Botswana. Through a survey conducted among 800 randomly selected individuals representing diverse genders in Botswana, with an 80% response rate, this study sheds light on the factors that hinder the uptake of insurance products in the country. The findings indicate that the low adoption of insurance products in Botswana can be attributed, at least in part, to various factors including low income, pervasive poverty, limited insurance awareness and education, and inadequate regulatory oversight.